Design of a Highly Efficient Subwavelength Antireflective Structure for Solar Cells - Lin Chen; Zhao Huang (International Journal of Optics)
An efficient optical antireflective (AR) structure plays a vital role in high-performance thin-film solar cells. Here, we design a surface relief AR structure consisting of a two-dimensional (2D) array of a subwavelength ring and pillar-shaped feature, capable of suppressing optical reflection over a wide spectral window of the solar spectrum. Our simulations show that the weighted average reflectance of the subwavelength AR structure is as low as 4.2% in the 400–1100 nm spectral range in the normal incidence condition and almost 10-fold reduction compared with a bare silicon surface. When placed on the front side of a simple Si thin-film photovoltaic solar cell, this subwavelength AR structure leads to an improved light absorption with simulated results showing an increase of 53% short-circuit current compared to a flat solar cell. Besides, our simulations show that this AR structure could, in principle, perform well against reasonable fabrication errors.